STEAM APPROACH USING INQUIRY LEARNING MODEL ASSISTED BY LIVEWORKSHEET TO IMPROVE LITERACY MATHEMATICS FOR FOURTH GRADES ELEMENTARY SCHOOL STUDENTS - Yulaikha, Kholisa Nur Putri; Rusnilawati, Rusnilawati (PROGRES PENDIDIKAN, 2025)
Education is a quite important aspect for every individual, especially in elementary school. This is due to carrying out life in the future in a global era that is full of challenges. So there needs to be awareness from everyone regarding the existence developments, thus learning patterns that are oriented towards technology-based learning needed. The aim of this research was to analyze the role of the STEAM (Science, Technology, and Mathematics) model in learning activities in elementary schools so that students can have critical thinking skills and encourage improving mathematical literacy skills IV at SD Negeri Trosemi 02 Gatak, Sukoharjo in cycle II. The research methods used to collect data are in the form of observation, and documentation. From the research carried out, it was found that: By implementing the STEAM approach with the Inquiry Learning model assisted by Liveworksheets, it can improve mathematical literacy and learning outcomes in Fourth grades students. Average percentage of students ' classical learning increased from cycle I by 83.33% to 94.4% in cycle II.